Assessing Delayed Collapse Risks in Load-Bearing Reinforced Concrete Walls Exposed to Parametric Fires: A Numerical Investigation - Guergah Cherif; Baghdadi Mohamed; Dimia Mohamed Salah; Antonio Marcos de Oliveira Siqueira; Júlio César Costa Campos (The Journal of Engineering and Exact Sciences)
This study delves into the thermo-mechanical analysis of structures exposed to fire, focusing on the evolution of gas temperatures, thermal distribution in structural members, and mechanical behavior during fire scenarios. Traditional prescriptive approaches assume a monotonically increasing temperature, while contemporary performance-based designs incorporate both heating and cooling phases for a more realistic fire resistance assessment. The critical aspect of this research is the modeling of the fire's cooling phase, which, though not commonly practiced in design offices, is essential for evaluating the risk of delayed structural collapse. Utilizing the finite element program SAFIR, numerical simulations were conducted on reinforced concrete walls to investigate their behavior during and post-cooling phase. The findings indicate potential failure not only during the cooling phase but also after the fire has subsided and temperatures have returned to ambient levels. This highlights delayed temperature increases in the core of the element and the consequent loss of concrete strength during cooling as key mechanisms of failure. A parametric study was undertaken, examining various fire scenarios, wall geometries, load levels, wall heights, adjacency, and boundary conditions. The results underscore that short-duration fires pose the most significant risk for delayed failure, particularly for simply supported walls. Additionally, the study scrutinizes the mechanical properties of materials across the heating and cooling phases. This investigation underscores the necessity of incorporating cooling phase analyses in fire resistance evaluations to mitigate the risk of delayed collapses. The insights gained aim to inform safer structural designs and enhance fire safety protocols, emphasizing the importance of realistic fire modeling in performance-based design methodologies.